(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
This article explores the strategic goals of the tsarist regime and the colonial nature of the resettlement policy in connection with the study of the place of the resettlement policy pursued by the Russian Empire in order to colonize Turkestan, including the Fergana region